Career Dynamics of Open University Lecturers - Rizka Furqorina; Kamari; Mohammad Iqbal Firdaus (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze lecturer career development with organizational commitment as a mediating variable. This study was conducted on lecturers at the Open University (UT). Data as of 2023, the number of lecturers at the Open University was 708 lecturers, with a breakdown of 430 lecturers assigned to the Central UT and 278 lecturers assigned to regional units (UT Daerah) (UT Personnel, 2023). In 2023, UT registered 525,419 students. Because UT students are spread throughout Indonesia in Regional UTs, lecturers are also placed in Regional UTs to assist in the implementation of education at Regional UTs. The implementation of education at UT also involves external parties as tutors. The role of lecturers at UT is slightly different from other conventional universities. Lecturers at UT, especially Lecturers at Regional UTs, participate more in administrative activities for distance learning. This results in a reduced academic atmosphere for lecturers. The problem faced by lecturers at UT is the less than optimal career development. This can be seen from the lecturer's rank and their activities and productivity. The functional position ratio of lecturers at UT is dominated by Lecturers (52.12%), followed by Assistant Experts (22.74%). Furthermore, lecturer activity and productivity at UT remain low, particularly those related to the Tri Dharma (Three Pillars of Higher Education), particularly those related to research and community service. In 2021, the number of funded research output articles was 246, with 60 community service outputs, and 80 independent research articles. These numbers are lower than the number of lecturers. This low career development can be caused by organizational support, work motivation, job satisfaction, and organizational commitment for lecturers. This study uses primary data. Research on the determinants of lecturer careers at Universitas Terbuka is important because lecturer careers are one of the factors influencing lecturer activity and productivity in implementing the Tri Dharma of Higher Education, which ultimately contributes to the institution.